Culture, control, confusion and contempt: A case study of the University of Nottingham Students’ Union. - Jackson, Emily (2018)
This dissertation will analyse the different ways that culture can be interacted with in an organisation and will comment on the relationships which can root from these interactions. I will explore the unclear nature of the term ‘culture’ and how the ambiguity of its definition can affect the relationships people have with the values of the business. The piece considers that an organisation’s culture is not homogenous and incorporates contradictions, paradoxes, ambiguities and confusion. My specific focus is the culture inside The University of Nottingham Students’ Union and how the culture created and controlled by management can differ from the culture visible within the Union. The piece will discuss whether culture is something which an organisation can possess or whether it is something that is incorporated into the makeup of the organisation. The ambidextrous nature of modern organisations will also be considered while discussing this topic. The two research questions will aim to delve into all levels of an organisation to assess the culture from top to bottom in order to achieve a well-rounded insight into Nottingham Students’ Union. Firstly, ‘How is culture utilised by management as a tool to influence and regulate organisational behaviour?’ Secondly, it will consider ‘How are values interpreted, put into practice and resisted by employees?’. The research approach was based on grounded theory, with data derived from eighteen semi-structured, qualitative interviews. The data was collated and then analysed thematically. The results widen the knowledge of the use of values in the performance management process and raise questions as to whether this is an effective or appropriate practice. The data also demonstrates that the ambiguous nature of culture is a key concept of its role within an organisation. When studying the Students’ Union as a case study it was clear that the organisation ‘has’ an espoused culture carefully constructed by management. However, within this there are numerous organic sub-cultures which represent what the culture ‘is’. This piece argues that culture is a fundamentally complex concept and that a new focus is needed when studying modern, ambidextrous organisations. The findings of other studies which explore the relationship between ambiguity and culture, as well as my own work, have serious implications for organisational, cultural management practices.